The Effect of Addition of Palm Oil Dry Waste Against Growth Rate of Sawi Plant (Brassica rapa) On Learning Environmental Knowledge - Azwar, Edi (International Journal for Educational and Vocational Studies, 2020)
The Utilization of sludge oil palm processing plant is still not optimal, therefore it is necessary to study the use of sludge as an alternative supply of nutrients in the soil that is used as an additional planting medium. This research contributes to environmental knowledge courses according to the syllabus and RPS and the output products of this study are learning modules. This study aims to determine the effect of the addition of palm oil dry mud waste to the growth rate of mustard plants (Brassica rapa) on the study of Environmental Knowledge, and to compile the module as the development of teaching materials from the Environmental Knowledge course module. This study used a completely randomized design with six treatments and four replications. The results of this study can be concluded that the administration of sludge is very influential in increasing nutrient and growth of mustard plants, namely: plant height (cm), leaf surface area (cm2), number of leaf strands, and stem length (cm).